British Freemasonry, 1717-1813, edited by Róbert Péter - Clements, Diane (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2019)
Reseña de British Freemasonry, 1717-1813, editado por Róbert Péter. Londres: Routledge, 2016. 2396 páginas. ISBN-13: 978-1138100190. ISBN-10: 1138100196.